Evaluation of enrofloxacin and oxytetracycline to eliminate persistent Anaplasma marginale infection in cattle - Flowers, Macy R. (Kansas State University, 2021)
Bovine anaplasmosis is a tick-borne bacterial disease of cattle caused by the rickettsial pathogen Anaplasma marginale. Common clinical signs of anaplasmosis include anemia, lethargy, pyrexia, and death. Antimicrobial treatment of anaplasmosis has historically relied on tetracycline injectables such as oxytetracycline; however, a new antimicrobial injectable Baytril® 100-CA1 (enrofloxacin), in a different antimicrobial class (fluorquinolone), was recently granted conditional approval for the treatment of clinical anaplasmosis. In most cases, animals infected with A. marginale survive infection with or without treatment intervention and remain carriers of A. marginale, serving as infection reservoirs. In some operations, producers desire to eliminate A. marginale infection to reduce transmission risk, alleviate associated disease management costs, and improve chances for herd or individual animal (e.g. seed stock, embryo transfer animals) profitability. Despite increasing desire for protocols to clear cattle of A. marginale infection, no drugs currently have an indication for elimination of A. marginale infection. This study was designed to investigate the efficacy of enrofloxacin and oxytetracycline to eliminate A. marginale infection in persistently infected steers. Fourteen Holstein steers previously inoculated with the Virginia or KS2 A. marginale strain and confirmed positive using a PCR test targeting the A. marginale Major Surface Protein 5 gene were allocated to treatment groups receiving injections of enrofloxacin (Baytril® 100-CA1) or oxytetracycline (Bio-Mycin® 200). The recommended dosage for each treatment (Bio-Mycin® 200 at 4.5 mL/100 lb, 10 mL/injection site; and, Baytril® 100-CA1 at 5.7 mL/100 lb, 20 mL/injection site) was administered subcutaneously for five consecutive days (this repetitive dosing scheme is off-label and was used for experimental purposes only). Blood samples were collected daily during treatment and twice weekly following the last treatment to monitor A. marginale infection status using the quantitative msp5 PCR assay and serostatus using a commercial cELISA. All seven steers receiving oxytetracycline and five of the seven steers receiving enrofloxacin remained positive for A. marginale infection. Both steers in the enrofloxacin group where infection was cleared were infected with the A. marginale VA strain. Injection site reactions were observed for two steers treated with oxytetracycline. Further refinement of an antimicrobial-based A. marginale infection elimination protocol that considers drug, dosing intervals, and A. marginale strain diversity is needed to provide producers options to reduce anaplasmosis transmission potential in their herd and retain valuable stock.
Keywords: Anaplasma marginale; Oxytetracycline; Enrofloxacin; Bovine anaplasmosis